Epstein-Barr virus latent membrane protein-1 expression in Hodgkin lymphoma (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
Expression of latent membrane protein-1 of Epstein-Barr virus is documented in Hodgkin lymphoma indicating its relationship in disease process. A total of 50 cases of Hodgkin lymphoma were analyzed for latent membrane protein-1 expression by immunohistochemistry. The mean age was 28.7 years with male predominance. Mixed cellularity classical Hodgkin lymphoma was the commonest subtype (50% cases). Out of 50 cases, 48% cases were found positive for latent membrane protein. Of the five histologic subtypes, all cases of lymphocyte depleted classical Hodgkin lymphoma showed positivity which was followed by 60% positivity of mixed cellularity classical Hodgkin lymphoma. Association of latent membrane protein-1 expression in relation to different age group, site of involvement and subtypes of Hodgkin lymphoma were found statistically insignificant while latent membrane protein-1 expression was significantly higher in male than female.